2007
DOI: 10.1289/ehp.10286
|View full text |Cite
|
Sign up to set email alerts
|

Does Short-Term Exposure to Mobile Phone Base Station Signals Increase Symptoms in Individuals Who Report Sensitivity to Electromagnetic Fields? A Double-Blind Randomized Provocation Study

Abstract: BackgroundIndividuals with idiopathic environmental illness with attribution to electromagnetic fields (IEI-EMF) believe they suffer negative health effects when exposed to electromagnetic fields from everyday objects such as mobile phone base stations.ObjectivesThis study used both open provocation and double-blind tests to determine if sensitive and control individuals experience more negative health effects when exposed to base station-like signals compared with sham.MethodsFifty-six self-reported sensitive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
119
4
14

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 111 publications
(144 citation statements)
references
References 6 publications
7
119
4
14
Order By: Relevance
“…A GSM study by Huber et al [2003] showed a reduction in HR during waking and stage 1 sleep, whereas, Braune et al [2002] and Tahvanainen et al [2004] found no effect of GSM-EMF on the HR in randomized crossover trials. In contrast to our results, Eltiti et al [2007Eltiti et al [ , 2009 did not find an effect on HR using a base station-like UMTS signal, which had a different carrier frequency of 2020 MHz and was continuous. Based on the literature cited, we conclude that the possible influence of RF exposure on the HR is still unclear.…”
Section: Medium-term Changescontrasting
confidence: 99%
See 1 more Smart Citation
“…A GSM study by Huber et al [2003] showed a reduction in HR during waking and stage 1 sleep, whereas, Braune et al [2002] and Tahvanainen et al [2004] found no effect of GSM-EMF on the HR in randomized crossover trials. In contrast to our results, Eltiti et al [2007Eltiti et al [ , 2009 did not find an effect on HR using a base station-like UMTS signal, which had a different carrier frequency of 2020 MHz and was continuous. Based on the literature cited, we conclude that the possible influence of RF exposure on the HR is still unclear.…”
Section: Medium-term Changescontrasting
confidence: 99%
“…Of three published studies on the effects of GSM exposure on HR, two found no effect [Braune et al, 2002;Tahvanainen et al, 2004], while one showed a small reduction in HR [Huber et al, 2003]. No effects were found in two studies using UMTS exposure [Eltiti et al, 2007[Eltiti et al, , 2009.…”
Section: Introductionmentioning
confidence: 91%
“…The WHO established the International EMF Project in 1996 to assess the scientific evidence of any possible health effects from EMR in the frequency range -0 to 300 GHz. In May 2006, WHO even released a fact sheet on "Electromagnetic fields radiation and public health: Base stations and wireless technologies" wherein it held that there is no convincing scientific evidence that the weak RF signals from wireless networks and mobile phone towers cause adverse health effects considering the very low exposure levels and results collected from the research [10][11][12] .…”
Section: Studies On the Effects Of Emfmentioning
confidence: 99%
“…Reported prevalence rates of electromagnetic hypersensitivity (EHS), which refers to the attribution of symptoms to exposure of RF EMFs, ranged from 1.5 to 10% in various population-based studies, with the majority of participants complaining of sleeping disorders and headaches. [40][41][42][43][44][45][46] Several laboratory studies have been conducted to investigate the association between RF exposure from mobile phones and the occurrence of subjective health complaints. On the other hand, studies conducted in Saudi Arabia, 47 Egypt, 48 and Poland 49 reported associations between mobile phone use and headache, fatigue, dizziness, tension, difficulties with concentration and sleep disturbances.…”
Section: Non-cancer Emf Effects Of Mobile Phone Usementioning
confidence: 99%
“…The health concerns mentioned with respect to RF-EMF exposure from mobile phone base stations include sleeping disturbances, headaches and various non-specific health symptoms among people living in proximity to the stations. [42][43][44][45][46] RF exposures from base stations differ from those associated with mobile phone use, mostly because they are directed at the whole body and can affect everyone. Even though exposure from base stations is more continuous by comparison, it is several orders of magnitude lower than exposure from mobile phones.…”
mentioning
confidence: 99%